1997
DOI: 10.1042/cs0930181
|View full text |Cite
|
Sign up to set email alerts
|

Cough Frequency and Cough-Receptor Sensitivity are Increased in Man at Altitude

Abstract: 1. Travellers to high altitude often complain of paroxysmal cough, which has not been previously investigated. We recorded overnight cough frequency and cough-receptor sensitivity to inhaled citric acid in a group of climbers travelling to 5300 m or higher. 2. Cough frequency, monitored in ten subjects, increased from a median of 0 coughs at sea level (range 0-1) to 5 coughs at 5000 m (range 0-13) and to over 60 coughs in subjects ascending to 7000 m. Citric acid cough threshold, measured in 42 subjects, was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…The authors have previously [6] demonstrated a significant increase in the frequency of nocturnal cough and a decrease in the CACT in a group of 42 subjects ascending to Everest Base Camp at 5,300 m in the Nepalese Himalaya. The changes in NCF were most obvious in a subgroup of three climbers ascending to 7,000 m or above.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors have previously [6] demonstrated a significant increase in the frequency of nocturnal cough and a decrease in the CACT in a group of 42 subjects ascending to Everest Base Camp at 5,300 m in the Nepalese Himalaya. The changes in NCF were most obvious in a subgroup of three climbers ascending to 7,000 m or above.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from a previous study [6], it was estimated that nine subjects would be needed to demonstrate a significant fall in the cough threshold with a study power of 80% [37]. It was only possible to accommodate eight subjects in the chamber, and a number of data points were missed owing to either subject illness or logistical problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations